Fiqh learning strategies in developing student character through islamic religious education at MA Ma'rif Pandaan Durensewu - Wibawa, Adnan; Jamhuri, M. (At- Ta'lim : Jurnal Pendidikan, 2025)
Islamic religious education, especially Fiqh, has an important role in shaping the character of students amid the rampant moral problems in society. At MA Ma’rif Pandaan Durensewu, Fiqh instruction not only focuses on teaching Islamic law but also aims to develop students' religious, disciplined, honest, and responsible character. This study employs a qualitative method with a case study approach to deeply investigate the Fiqh learning strategies implemented at the school. Through direct observation and interviews with Fiqh teachers on November 6, 2024, this research explores how learning strategies involving habituation, role modeling, and worship activities can foster Islamic character in students. The results of the study show that the learning strategies implemented at MA Ma’rif Pandaan Durensewu successfully instill values of discipline, responsibility, and Islamic morals through various activities such as congregational prayers, Qur'an recitation, and dhikr. Additionally, the teachers' role modeling of honesty, responsibility, and discipline significantly contributes to shaping students' noble character. However, there are several challenges encountered, such as the lack of adjustments to students' varying levels of understanding, limited educational technology, and restricted time for in-depth material discussions. Despite these challenges, Fiqh teachers at MA Ma’rif Pandaan Durensewu continuously strive to refine learning strategies to be more effective in fostering students' Islamic character.